2015
DOI: 10.1136/sextrans-2014-051859
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of standard therapies againstUreaplasmaspecies and persistence among men with non-gonococcal urethritis enrolled in a randomised controlled trial

Abstract: Objective U. urealyticum biovar 2 (UU-2) but not U. parvum (UP) has been associated with non-gonococcal urethritis (NGU), but little is known about species-specific responses to standard therapies. We examined species-specific treatment outcomes and followed men with treatment failure for 9 weeks. Methods From May 2007-July 2011, men aged ≥16 attending an STD clinic in Seattle, Washington with NGU (urethral discharge or urethral symptoms plus ≥5 PMNs/HPF) were enrolled in a double-blind, randomized trial. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…U. urealyticum is moderately sensitive to 14‐membered macrolides. In general, urogenital M. hominis , U. parvum and U. urealyticum can be difficult to eradicate in many individuals because of true antimicrobial resistance but also because of lower activity of the antimicrobials at low pH and lack of bactericidal activity . Additionally, suboptimal antimicrobial susceptibility testing methods, including many commercial kits, are frequently used .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…U. urealyticum is moderately sensitive to 14‐membered macrolides. In general, urogenital M. hominis , U. parvum and U. urealyticum can be difficult to eradicate in many individuals because of true antimicrobial resistance but also because of lower activity of the antimicrobials at low pH and lack of bactericidal activity . Additionally, suboptimal antimicrobial susceptibility testing methods, including many commercial kits, are frequently used .…”
Section: Discussionmentioning
confidence: 99%
“…In general, urogenital M. hominis, U. parvum and U. urealyticum can be difficult to eradicate in many individuals because of true antimicrobial resistance but also because of lower activity of the antimicrobials at low pH and lack of bactericidal activity. 4,27,[78][79][80] Additionally, suboptimal antimicrobial susceptibility testing methods, including many commercial kits, are frequently used. 80 The extensive treatment of these commonly colonizing commensals with suboptimal antimicrobial regimens selects for antimicrobial resistance in these bacteria and in many of the more severe bacterial 'true' STI agents as well as in the general microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of azithromycin is different for U. parvum and U. urealyticum . In one study, after treatment with azithromycin, persistent urethritis was more commonly observed in patients infected with U. urealyticum than in those infected with U. parvum …”
Section: Therapeutic Options For Genital Ureaplasma Infection In Pregmentioning
confidence: 99%
“…However Sviben et al 's data suggest that detection in men could reach worthwhile levels6 in symptomatic men. The question of what pathogens we should test for is further complicated by an RCT by Khrosopour et al ,7 showing that while persistence of ureaplasma species was common after treatment with standard therapies, it was not associated with persistent urethritis.…”
mentioning
confidence: 99%